Myosin 1F Regulates M1-Polarization by Stimulating Intercellular Adhesion in Macrophages - Piedra-Quintero, Zayda L.; Serrano, Carolina; Villegas-Sepúlveda, Nicolás; Maravillas-Montero, José L.; Romero-Ramírez, Sandra; Shibayama, Mineko; Medina-Contreras, Oscar; Nava, Porfirio; Santos-Argumedo, Leopoldo (Frontiers in Immunology, 2019)
Intestinal macrophages are highly mobile cells with extraordinary plasticity and actively contribute to cytokine-mediated epithelial cell damage. The mechanisms triggering macrophage polarization into a proinflammatory phenotype are unknown. Here, we report that during inflammation macrophages enhance its intercellular adhesion properties in order to acquire a M1-phenotype. Using in vitro and in vivo models we demonstrate that intercellular adhesion is mediated by integrin-alphaVbeta3 and relies in the presence of the unconventional class I myosin 1F (Myo1F). Intercellular adhesion mediated by alphaVbeta3 stimulates M1-like phenotype in macrophages through hyperactivation of STAT1 and STAT3 downstream of ILK/Akt/mTOR signaling. Inhibition of integrin-alphaVbeta3, Akt/mTOR or lack of Myo1F attenuated the commitment of macrophages into a pro-inflammatory phenotype. In a model of colitis, Myo1F deficiency strongly reduces the secretion of proinflammatory cytokines, decreases epithelial damage, ameliorates disease activity and enhances tissue repair. Together our findings uncover an unknown role for Myo1F as part of the machinery that regulates intercellular adhesion and polarization in macrophages.